Neonatal hearing screening in newborns of pregnant women diagnosed with syphilis - Wunsch, Caroline; Unchalo, Adriana Laybauer Silveira; Anschau, Cassandra Caye; Saltiél, Debora Ruttke Von; Kochhan, Denise Saúde; Teixeira, Adriane Ribeiro (Seven Editora, 2024)
Introduction: Congenital Syphilis is considered a Risk Indicator for Hearing Impairment (RIHI) by the Joint Committee on Infant Hearing (JCIH), making neonates exposed to this indicator more susceptible to this problem. Objective: To analyze the results of Neonatal Hearing Screening (NHS) in neonates whose mothers were diagnosed with syphilis during pregnancy. Methods: Cross-sectional and retrospective study. The following tests were performed: Transient Evoked Otoacoustic Emissions (TOAE) and/or Automatic Brainstem Auditory Evoked Potential (AABR). Results: A total of 169 medical records of newborns were analyzed, divided into two groups: syphilis (neonates of adequately treated mothers) and syphilis requiring intermediate hospitalization (inadequately treated mothers). The mean age at the first test was 2 days, with a predominance of males. In the comparative analysis between the right and left ears, there was no significant difference between the pass/fail results, and the pass result prevailed in both ears. The AABR was the most used in the test and retest in both groups. Of the 169 neonates, 37 failed the hearing screening and 29 were retested. In the retest, three individuals in the sample remained with the altered test and only one continued the diagnostic process, initially identifying conductive hearing loss and later results considered normal in the auditory evoked potential. Conclusion: The results of the study indicate that, in the sample studied, there was no association between the maternal diagnosis of syphilis and neonatal hearing loss, although syphilis is an important indicator of risk for hearing loss. DOI:https://doi.org/10.56238/sevened2024.018-060